2009
DOI: 10.2355/isijinternational.49.521
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Electromagnetic Stirring in Steel Billet Caster by Using Image Processing Technique for Improvement in Billet Quality

Abstract: Fig. 1. Schematic diagram of billet sample (cross section 130ϫ130) collected for ultrasonic C scan testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 7 publications
(7 reference statements)
0
27
0
1
Order By: Relevance
“…[2,4,5,10,[17][18][19][20][21][22] However, only one previous research reported data on the deflection angle under the influence of M-EMS. In that work, [23] it is indicated that the deflection angle is effected by the solute and temperature gradients induced by fluid flow not by the EM force directly and 60 pct of the imposed electromagnetic force disappears due to the interaction of 3D flow, for example, from the submerged entry nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…[2,4,5,10,[17][18][19][20][21][22] However, only one previous research reported data on the deflection angle under the influence of M-EMS. In that work, [23] it is indicated that the deflection angle is effected by the solute and temperature gradients induced by fluid flow not by the EM force directly and 60 pct of the imposed electromagnetic force disappears due to the interaction of 3D flow, for example, from the submerged entry nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…There are many inspection systems, but machine visionbased surface defect detection has been applied widely in steel production 2) because this approach is advantageous in terms of its repeatability, consistency, and costs. A number of machine vision-based methods have been proposed to improve steel quality and the efficiency of manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The relation between the maximum electromagnetic force and the imposed current is plotted in Figure 3(a). According to the electromagnetic theory, 1) the Lorentz force F is directly proportional to B 2 , and BϰI (stirring current). Therefore, the Lorentz force is proportional to I 2 , i.e., FϰI 2 .…”
Section: Numerical Investigationmentioning
confidence: 99%
“…By controlling the M-EMS current and frequency, stirring intensity in the liquid pool can be controlled. A number of researchers [1][2][3][4][5][6][7][8][9] found that M-EMS reduces center porosity, shrinkage cavity and macro-segregation, and that it removes non-metallic inclusions in the mold owing to centripetal force.…”
Section: Introductionmentioning
confidence: 99%